Nuevas citas de Monocotiledóneas para la provincia de Granada (Sur de España). - Vizoso, María Teresa; Baena, Laura; Navarro, Francisco Bruno (Acta Botanica Malacitana, 2002)
New floristic records of Monocotyledons for Granada province (S Spain). Palabras clave. Corología, Monocotiledóneas, Granada. Key words. Corology, Monocotyledons, Granada, Spain.